Screening of HIV sero positive women for cervical abnormalities - Chauhan, Meenakshi B.; Chaudhary, Sushila; Singh, Sunita; Juneja, Manasi; Nanda, Smiti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cancer cervix is a leading cause of death among women worldwide. Detection of cervical cancer in precancerous stage is 100% curable. Screening with Pap smear has reduced mortality by cervical cancer in developed countries many folds. The objective of the study is to determine prevalence of Cervical Intraepithelial Neoplasia (CIN) in HIV infected women and observe for associated lower genital infections and their correlation with CD4 counts. Methods: The present study is a cross-sectional observational study conducted at PGIMS, Rohtak, Haryana for a period of 18 months. 150 HIV patients and 150 age related control cases were taken. Pap smears were taken and analyzed for cervical abnormalities and genital infections. Results: Of the 300 Pap smear 22 (7.3%) has squamous intraepithelial abnormalities and 278 (92.7%) negative for intra epithelial abnormalities. Prevalence of cervical intraepithelial abnormities among HIV positive 12% while among HIV negative it is 2.7%. Cervical intraepithelial abnormalities were found in 40% and 3.5% of patients with CD4 count <200 and >200 respectively. Conclusions: HIV increases the risk of cervical abnormalities. Frequent screening of these patients for cervical cancer is needed.